The Influence of Service Timeliness and Product Quality on Purchase Intention: The Mediating Role of Consumer Trust in Sweet City Tofu MSME, Gunung Putri District - Dara Juwita; Agus Sudigdo (Journal AGENCY, 2025)
This study aims to examine the effect of on-time availability of service and product quality on consumers' purchase intention, with consumer trust as an intervening variable, at the Tahu Kota Manis MSME in Gunung Putri District. Purchase intention is influenced by many factors, including the timely availability of products, consistent product quality, and the level of consumer trust in the product. The sample of this study consisted of 97 MSME consumers, determined using the Lemeshow formula. Data collection was carried out through questionnaires distributed both offline and online. The data were analyzed using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS-SEM) approach. The results show that both on-time availability of service and product quality have a positive and significant effect on consumer trust. On-time availability of service also has a direct and significant effect on purchase intention. However, product quality does not have a direct significant effect on purchase intention. Consumer trust has a significant effect on purchase intention and significantly mediates the effect of both service availability and product quality on purchase intention. Therefore, consumer trust becomes a key variable that strengthens the relationship between service and quality in influencing consumer purchase intention. This study recommends that MSME actors focus more on maintaining service reliability and product quality consistency to enhance consumer trust and purchase intention.